Chapter The Community Education Program: A Reflection on Good Practice in the USA - Douglas, Miriam (Studies on Adult Learning and Education, 2020)
This good practice essay puts the Community Education Program (CEP) as a focus for comparison between West Virginia (USA) and Germany/European Union (EU). The essay is a combination of reflections on qualification frameworks, learning outcomes, lifelong learners/learning, transnational organisations, the Scottish Framework, a number of good practices, and accreditation from a research and practical perspective. Despite substantial research efforts, a national qualifications framework (NQF) or accrediting body for the CEP could not be identified in the US. The goal is to continue research on a national and international level. In the meantime, the good practice efforts, established through various features, continue to apply.